A survey of men's classic and trendy casual wear based on the sales turnover of selected garment retail stores in the metropolitan and provincial areas - Pascual, Robin Michael Bautista; Florendo, Racquel B. (2000.)
The renewed emphasis on men's fashion as observed through the different types of media prompted the study of clothing preferences of male consumers on casual wear. Moreover, to find out if ths renewed fashion consciousness has spread, the study also sought to determine if clothing preferences are the same in the metropolitan and provincial areas or not. Findings will be a valuable reference not only to garment retailers but to other types of business establishments and the consumers as well. The descriptive method of research was used for analyzing data. Survey questionnaires were distributed to the main offices of five (5) purposively selected garment retail companies with branches in both SM City North Edsa, Quezon City and N.E pacific Mall, Cabanatuan City, and carry the classic casual and trendy casual definitions of the study for men's casual wear. The garment retail stores' casual wear sales movement in both areas classified as Slow, Moderate and Fast were analyzed and summarized. The ranking of the different factors affecting clothing preferences of male consumers as perceived by the managers were tabulated. Results and findings of the study revealed that metropolitan male consumers prefer classic casual wear to trendy casual ones and that these consumers commonly buy classic T-shirts, polo shirts and jeans. In contrast, provincial male consumers prefer the trendy casual wear to classic casual ones ans commonly buy trendy jeans, sport shirts, T shirts and slacks. This shows that the classic casual wear, in general, are most saleable because population in the metropolis is much bigger than the province. The findings also showed that the popularity of the brand is the most influential factor affecting clothing preferences of male consumers in both areas. Trend ranked 2nd, advertisement 3rd, price and peers both ranked 4.5, financial status, 5th, media 6th, and aesthetic details ranked 7th or is the least influential factor affecting clothing preferences of male consumers. The study implies that even if classic casual garments are most saleable, trendy casual garments still have room for creativity and innovation. For in time, frequent best sellers in trendy casual items will be part of the classic casual ones in the near future. What may be considered trendy today may become the classics of tomorrow.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Men' clothing